Macroeconomic Policies and Smuggling : An Analysis of Illegal Oil Trade in Nigeria - Wang, Jian-Ye (IMF Working Papers; Working Paper ;, 1994)
Based on a simple model, the paper provides an explanation for illegal oil trade between Nigeria and its neighboring countries. The analysis focuses on the linkages between the level of smuggling and changes in the Government's fiscal, monetary, and domestic pricing policies. It is shown that smuggling has implications for inflation and currency depreciation. A vicious circle emerges when financial policies are expansionary and policy makers attempt to hold the domestic sale price of oil constant. Macroeconomic indicators of Nigeria over the period 1986-1993 appear to support the predictions of the model. Policy implications of the analysis are also noted.